2022
DOI: 10.3390/buildings12081067
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Barriers to Building Information Modelling (BIM) Implementation in Wood Construction Projects: Evidence from the Swedish Context

Abstract: Building information modelling is gradually being recognised by the architecture, engineering, construction, and operation industry as a valuable opportunity to increase the efficiency of the built environment. Focusing on the wood construction industry, BIM is becoming a necessity; this is due to its high level of prefabrication and complex digital procedures using wood sawing machines and sophisticated cuttings. However, the full implementation of BIM is still far from reality. The main objective of this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Although the benefits and applications of BIM as described in the literature appears to be very promising, however, the literature also revealed that these benefits are not fully realised, and the applications are not all being used in the current status of the construction industry (Arrotéia et al , 2022; Deng, 2022; Mahmoud et al , 2022). There is a positive correlation between the BIM level of implementation and the extent of use within a project (Gharaibeh et al , 2022b; Oraee et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefits and applications of BIM as described in the literature appears to be very promising, however, the literature also revealed that these benefits are not fully realised, and the applications are not all being used in the current status of the construction industry (Arrotéia et al , 2022; Deng, 2022; Mahmoud et al , 2022). There is a positive correlation between the BIM level of implementation and the extent of use within a project (Gharaibeh et al , 2022b; Oraee et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A disparity between the conceptual understanding of BIM technology and its practical application has been acknowledged in the literature (Dowsett and Harty, 2019) (Gharaibeh et al , 2022b; Viliūnas and Migilinskas, 2021). The comprehensive vision of BIM, encompassing its potential, advantages and practical applications, has yet to be fully realized in practice (Bosch-Sijtsema et al , 2017; Mahmoud et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Under the category "Organizational Resistance and Cultural Change", the implementation of AWP confronts significant barriers rooted in the human and cultural dimensions of organizational environments. The resistance to change emerges as a recurring theme, reflecting a deep-seated inertia within the corporate culture that is resistant to new methodologies, not only AWP but also many other practices and philosophies, such as lean construction, digital transformation, and others [7,23,[66][67][68][69][70][71]. This resistance is often coupled with concerns about disclosing trade secrets, which can inhibit the sharing of information necessary for effective AWP implementation [23].…”
Section: Organizational Resistance and Cultural Changementioning
confidence: 99%
“…Having a thorough understanding of the business benefits of BIM can assist organizations in making informed decisions about whether to invest in BIM technology and how to implement it effectively (Ardani et al, 2022;Cucuzza et al, 2022;Gharaibeh et al, 2022). An organization can evaluate the potential return on investment (ROI) and determine whether the benefits outweigh the costs by identifying the specific benefits that BIM can provide, such as cost savings, improved productivity and reduced errors.…”
Section: Introductionmentioning
confidence: 99%